Multi‐hop delay reduction for safety‐related message broadcasting in vehicle‐to‐vehicle communications. Issue 3 (1st February 2015) - Li, Xiaohuan; Hu, Bin‐jie; Chen, Hongbin; Li, Bing; Teng, Huanglong; Cui, Manman
Abstract : In vehicle‐to‐vehicle (V2V) communications, low delay and long propagation distance are very important for multi‐hop safety‐related message broadcasting. Most earlier studies focused on one‐hop broadcasting while little attention has been paid to multi‐hop delay and propagation distance. In this study, a new model for analysing the connectivity probability, average hop count and one‐hop delay of multi‐hop safety‐related message broadcasting in V2V communications is built, taking into account the following factors: propagation distance, one‐hop transmission range, distribution of vehicles, vehicle density, average length of vehicles and minimum safe distance between vehicles. Simulation results demonstrate that the proposed model can provide better performance in terms of multi‐hop delay and there exists an optimal one‐hop transmission range to minimise the multi‐hop delay. After that, A new scheme is proposed to track the optimal one‐hop transmission range by using a Genetic Algorithm. With this scheme, vehicles are allowed to adjust the one‐hop transmission range based on vehicle density to reduce the multi‐hop delay. The proposed scheme is validated by simulations using realistic vehicular traces.